2020
DOI: 10.1186/s12864-020-6690-1
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome resequencing reveals an association of ABCC4 variants with preaxial polydactyly in pigs

Abstract: Background: Polydactyly is one of the most common congenital limb dysplasia in many animal species. Although preaxial polydactyly (PPD) has been comprehensively studied in humans as a common abnormality, the genetic variations in other animal species have not been fully understood. Herein, we focused on the pig, as an even-toed ungulate mammal model with its unique advantages in medical and genetic researches, two PPD families consisting of four affected and 20 normal individuals were sequenced. Results: Our r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…The confidence regions and candidate gene proposed in our study differ from the results of Ma et al. 's study but are consistent with findings from studies in humans and other vertebrate species (Ma et al., 2020). These results not only suggest that the potential pathogenic mechanisms for preaxial and postaxial polydactyly in Large White pigs are distinct but also imply that the role of ZRS in LMBR1 for toe development is conserved across Large White pigs, humans and other animals.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The confidence regions and candidate gene proposed in our study differ from the results of Ma et al. 's study but are consistent with findings from studies in humans and other vertebrate species (Ma et al., 2020). These results not only suggest that the potential pathogenic mechanisms for preaxial and postaxial polydactyly in Large White pigs are distinct but also imply that the role of ZRS in LMBR1 for toe development is conserved across Large White pigs, humans and other animals.…”
Section: Resultssupporting
confidence: 90%
“…Referring to previous reports, we confirmed that the imputation accuracy exceeded 91.57% when using 80K chip data (Fuller et al., 2020). We examined the genotype of the previously reported missense mutation on ABCC4 in the high‐depth resequencing dataset using the igv software (Ma et al., 2020; Robinson et al., 2017). We found that the missense mutation was fixed as AA in our dataset, indicating that it is unlikely to be an associated locus in our study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations